Pengaruh Kombinasi Terapi Relaksasi Benson dan Murottal Al-Qur’an Terhadap Respiratory Rate pada Pasien Penyakit Paru Obstruktif Kronik (PPOK) - Senia Pangestu Luhur Cahya; Erna Melastuti; Ahmad Ikhlasul Amal (Jurnal Medika Nusantara, 2025)
Background: In Central Java, chronic obstructive pulmonary disease (COPD) is included in the top 10 causes of death and disease burden. COPD is a respiratory disorder that worsens over time. Benson's relaxation therapy combined with Qur'anic recitation is one of the non-pharmacological interventions that has the ability to affect the rate of breathing. Objective: This study aims to find out how Benson's relaxation therapy and Qur'an recitation simultaneously affect RR in COPD patients. Method: Without a control group, this research employed a pre-experimental design with a one-group pretest-posttest. The inclusion and exclusion criteria were used to pick a total of 18 samples using the purposive sampling approach. In order to examine the data, the Wilcoxon test and univariate and bivariate tests were used. Result: This research showed that before the intervention, the patient's respiratory rate was above normal, but then normalized after the intervention (p < 0.001). Conclusion: The combination of Benson relaxation therapy and Al-Quran recitation has a significant effect on the respiratory rate (RR) in COPD patients.